Simulation Analysis of Thermal Stress of Concrete Face Slab in Rock-fill Dam Based on Unsteady Field - GUAN Zhibao; LI Guoxiang (Renmin Zhujiang)
Based on unsteady thermal stress field method, this paper conducts the three-dimensionalfinite element construction simulation analysis on the face slab concrete of rock-fill dam in rockyhydro project and water supply project in Northwest Guizhou Province, mainly covering the changerules of unsteady temperature and stress distribution during the construction period of the faceslab, the elastic modulus of the cushion at the bottom of the face slab and the sensitivity of thepouring temperature of the face slab concrete to the thermal stress. The research results showthat: ①The larger the elastic modulus of cushion is, the greater the thermal stress of the faceslab concrete is; ②The lower the pouring temperature is, the smaller the thermal stress of theconcrete is; ③Considering the control of face slab crack, it is more economical and reasonableto control the pouring temperature of the face slab at the average air temperature. The researchresults can be as a reference for other similar projects.